Implementation of Human Resource Management at PMKS PT. Sinar Pandawa - Andriani Sahputri; Aninda Mahfadillah; Annio Indah Lestari Nasution (Journal of Indonesian Management, 2022)
The purpose of this study is to find out how the management of human resources is carried out at PMKS PT. Sinar Pandawa, namely knowing the recruitment system, employee training, employee assessment and supervision of employee attendance, as well as occupational safety and health. This study uses a descriptive research method with a qualitative approach. Data was collected by means of interviews and documentation, as well as using primary and secondary data. The results showed that in 2021 employees at PMKS PT. Sinar Pandawa numbered 107 people. Implementation of human resource management in PMKS PT. Sinar Pandawa is carried out with an employee recruitment system that is used through internal and external sources, conducting certified training, evaluating employees with 3 (three) aspects of assessment and monitoring employee attendance through the fingerprint attendance system. Then, the occupational safety and health that is implemented is by requiring employees to wear PPE (Personal Protective Equipment, as well as conducting socialization or counseling.